How (Ultra‐)Rare Gene Variants Improve Our Understanding of More Common Autoimmune and Inflammatory Diseases - Alexandre Belot; Maud Tusseau; Jade Cognard; Sophie Georgin‐Lavialle; Guilaine Boursier; Christian M. Hedrich (ACR Open Rheumatology, 2025)
The aim of this study was to explore the impact of rare and ultra‐rare genetic variants on the understanding and treatment of autoimmune and autoinflammatory diseases with a focus on systemic lupus erythematosus (SLE) and Behçet syndrome. This review summarizes current research on the monogenic causes of SLE and Behçet syndrome, highlighting the various pathways that can be responsible for these unique phenotypes. In monogenic SLE, the identification of complement and DNASE1L3 deficiencies has elucidated mechanisms of apoptotic body accumulation and extracellular nucleic acid sensing. Type I interferonopathies underline the specific role of DNA/RNA sensing and the interferon overexpression in the development of systemic autoimmunity. Other significant genetic defects include Toll‐like receptor hypersignaling and JAK/STATopathies, which contribute to the breakdown of immune tolerance. To date, genetic defects directly affecting B and T cell biology only account for a minority of identified causes of monogenic lupus, highlighting the importance of a tight regulation of mechanistic target of rapamycin and RAS (Rat sarcoma GTPase)/MAPK (mitogen‐activated protein kinase) signaling in lupus. In Behçet syndrome, rare variants in TNFAIP3, RELA, and NFKB1 genes have been identified, underscoring the importance of NF‐κB overactivation. Additional monogenic diseases such as ELF4, WDR1 mutations and trisomy 8 further illustrate the genetic complexity of this condition. Observations from genetic studies in SLE and Behçet syndrome highlight the complexity of systemic inflammatory diseases in which distinct molecular defects caused by single‐gene mutations can promote lupus or Behçet syndromes, often unrecognizable from their genetically complex “classical” forms. Insights gained from studying rare genetic variants enhance our understanding of immune function in health and disease, paving the way for targeted therapies and personalized medicine.